THE EFFECT OF JOB SATISFACTION AND WORK STRESS ON EMPLOYEE WORK PRODUCTIVITY CV AMANDA BROWNIES STEAMED MEDAN - Riska Winanda; Fitra Arlina Nasution; Deena Nikita Siregar; Dini Amelia Gabyani (Universitas Efarina, 2021)
Employee Productivity is the ability to obtain the maximum benefit from the facilities and infrastructure available to generate optimal output, if possible maximum. Increased job satisfaction of employees will have a positive impact for the company and vice versa if the stress levels of employees increase, which will impact negatively on the company and of course this will affect the level of employee productivity. This study aims to analyze the influence job satisfaction and stress on employee productivity in the CV. Amanda Brownies Steamed Medan. This research uses causal research that sought to prove a causal relationship between the variables in the form of influence through hypothesis testing using a sampling technique slovin formula as well as primary data in the form of questionnaires are processed using the program Statistical Product Service Solution (SPSS) version 22. Data analysis technique used is multiple linear regression analysis (Multiple Regression) and using test data quality, classical assumptions and hypothesis testing. The analysis showed adjusted R Square 0,990 or 99.00%. 829.673 with a confidence level of 5% level test Faccount = 829.673> Ftable = 2.79 then H0 and H1 accepted, so Job Satisfaction and Stress affects simultaneously (simultaneously) on Employee Productivity. While Job Satisfaction with tcount 8.288> ttable 1.676 and significant 0.000 <0.05, then H0 is rejected and H1 accepted and can be interpreted Job Satisfaction partial effect to the Employee Productivity and Stress variables with tcount -5.558 < ttable 1.676 and significant 0.000 <0.05, the stress has no effect partially on Employee Productivity, as tcount smaller than the value ttabel